Монтажна композиція в романах Дж. М. Кутзее: моделювання ігрового стилю - Ізотова, Наталя Павлівна; Izotova, N. P. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті з позиції ігрової стилістики встановлено особливості семантики та функціонування монтажної композиції в романах відомого південноафриканського письменника Дж. М. Кутзее. З’ясовано, що в лю¬дологічному ключі художній твір постає як ігрова система, усі елементи якої так чи інакше відбивають спосіб художнього мислення автора, його ставлення до життя і мистецтва. Гру, відповідно, розглянуто як певну авторську стратегію, що функціонує на різних рівнях художньої системи: від мовної гри до ігрової картини світу. Ідіостильовими рисами поетики монтажу в аналізованих романах Дж. М. Кутзее є дискретність, фрагментарність, деформація простору й часу, протиставлення вимислу та реальності, психологізм. Монтаж у композиційній структурі романів Дж. М. Кутзее виконує низку функцій: актуалізує тематичний план худож¬нього твору; створює нелінійну, фрагментарну оповідь; впливає на неоднозначність, алегоричність, енігма¬тичність сприйняття романів, слугує засобом характеризації персонажів, сприяє психологізації художньої оповіді. The article focuses on semantics and functioning of montage technique in J. M. Coetzee’s fiction from the perspective of ludostylistics. Within the framework of ludostylistics a literary text is viewed as a ludic system. The constituents of such a system, one way or another, represent the author’s creative thinking, his/her attitude towards life and art. The game in the text can be regarded, respectively, as the author’s strategy which functions on various levels of the artistic system: from the language game to the ludic picture of the world. Due to the creative, emotive, aesthetic and heuristic nature of game, it is considered to be an effective means of studying the author’s individual style. J. M. Coetzee’s ludic style can be modeled through the prism of montage technique. Montage is defined as a process of making the whole picture, film, or a piece of music or writing by combining parts of different pictures, films etc in an interesting and unusual way. J. M. Coetzee’s poetics of montage is characterized by the following features: discrete, fragmentary and inconsistent nature of episodes, time and space transformation, opposition between reality and fancy, psychologism. As a literary technique, montage performs several functions in J. M. Coetzee’s fiction: it develops the theme of the novel; produces a non-linear, fragmentary plot development; contributes to ambiguous, enigmatic, allegorical perception of the text; characterizes personages, creates psychologism of a literary narrative.
Montage in J. M. Coetzee’s Fiction: Modeling a Ludic Style
Keywords: гра; game; ігрова стилістика; ludostylistics; ігровий стиль; ludic style